A potência do cyborg no agenciamento de modos de subjetivação pós-identitários: conexões parciais entre arte, psicologia e gênero - Stubs, Roberta [UNESP]; Teixeira Filho, Fernando Silva [UNESP]; Peres, Wiliam Siqueira (Universidade Federal Fluminense, Departamento de Psicologia, 2014)
In line with a psychology more attached to the becoming [devenir] rather than tothe essence, the goal of this paper is to ground the importance of understandingsubjectivity as a process, mainly when regarding our current discussions aboutidentity and gender. After that, we do some linkage between art and psychology. Forus, art is understood as a powerfulmanner to encourage modes of subjectivation thathave difference as an inherited relation. Lastly, we draw our attention upon somefragments of the contemporaneous artist, Mathew Barney's work-of-art (specially,Cremaster), to see how it runs through the binaries of gender boundaries andlaunches post-identity lines of subjectivation.

Em consonância com uma psicologia mais afeita ao devir do que às essências, a proposta deste artigo é fundamentar a importância de se compreender a tradicional concepção de subjetividade enquanto um processo de subjetivação, principalmente no que tange as discussões sobre identidade e gênero na atualidade. Feito isso, traçamos algumas aproximações entre arte e psicologia, compreendendo a primeira como um potente dispositivo para favorecer modos de subjetivação que tenham a diferença como inerência relacional. Por fim, lançamos nossos olhares em alguns fragmentos da obra Cremaster do artista contemporâneo Mathew Barney para perceber o modo como a obra ultrapassa os binarismos de gênero e lança linhas pós-identitárias de subjetivação.
The power of cyborg in the assembling of modes of post-identitie subjectivation: partial connections among art, psychology and gender
Keywords: Post-identity; Cyborg subjectivity; Aesthetics subjectivity; Pós-identidade; Subjetividade cyborg; Subjetividade estéticasubjetividade estética